Research on glass imitation jade culture in the ancient Chinese Silk Road - Sai Huang; Ziyi Wang; Junyi Zhu (Scientific Reports)
Abstract This paper undertakes a multi-dimensional exploration of the glass imitation jade culture under the context of the ancient Silk Road, tracing the historical trajectory of glass manufacturing technology from West Asia to China, especially after the Han Dynasty, when the flourishing trade along the Silk Road facilitated the integration of foreign glass craftsmanship with China’s indigenous imitation jade tradition. This integration prompted Chinese glass artifacts to not only incorporate foreign techniques but also emphasize the texture and cultural symbolism of jade. Through systematic archaeological excavations and historical text analysis, this study delves into the unique phenomenon of glass imitation jade on the ancient Silk Road in China, providing detailed exposition on the formation, characteristics, and profound impact of this cultural practice. Imitation jade culture extends beyond physical forms, permeating material selection, technological innovation, and cultural symbol inheritance. As a gem of ancient Chinese craft art, the glass imitation jade culture offers valuable insights into understanding the aesthetic features of ancient cultures, cultural exchange patterns, and the evolution of craft technologies. This paper innovatively proposes that ancient glass-making practices imitation jade can serve as a new means to actively protect natural jade resources in modern times, offering a fresh perspective for the exploration and study of the Silk Road cultural heritage.